Exploring the multiple contributions of enset (Ensete ventricosum) for sustainable management of home garden agroforestry system in Ethiopia - Mesfin Sahle (Elsevier, 2021)
Although keystone species in the home garden agroforestry system provide multiple contributions to people, they have not been thoroughly researched, particularly in indigenous crops. Enset (Ensete ventricosum) is a domesticated home garden perennial crop in large parts of southern Ethiopia. This study explores the diverse contributions of enset in the Gurage socio-ecological production landscape in Ethiopia through geospatial, field surveys, and biophysical measurements. Nature's contribution to people (NCP) assessment framework has been considered to explore the societal benefits of the enset crop, and more than 25 contributions are identified in the landscape. Every part of the crop is essential for the local people. The range of contributions extends from food for humans and feeds for livestock to climate regulations and soil enrichment. Enset is a cultural asset of the community and contributes to enhancing the aesthetic quality of the landscape. However, their diverse uses have been decreasing due to socioeconomic changes and the lack of technological innovations. This decline can result in the loss of the home garden system, which eventually puts the community's food security at risk and the regulating and nonmaterial benefits being degraded. This study integrated the diverse tools to overcome the limited approaches of NCP assessment and scanned solutions for the sustainability of the enset farming system and to transform the food security in the region. Exploring such types of keystone species' diverse roles has indispensable for a better understanding of the agroecosystem's contributions and to drive transformative strategies for environmental sustainability.